Development of Students’ Akidah Akhlak Worksheet Using the Canva Application in Improving the Learning Ability - Ummu Habibah Rahmah; Jaenullah; Siti Roudhotul Jannah; Agus Setiawan; Tukiran (Edutechnium Journal of Educational Technology, 2023)
Technological developments require teachers to be more creative and innovative in carrying out the teaching and learning process. Teachers often use LKPD, a teaching material, but rarely pay attention to students' interest in reading it. LKPD is used so that the learning process is not teacher-centered. The development of LKPD was carried out considering technological advances, which are developing rapidly. The Canva application comes with a variety of attractive designs that make conveying information not dull. LKPD using the Canva application is packed with exciting pictures and stories as material reinforcement. The purpose of this study was to find out students' reading interest after using the Akidah Akhlak LKPD Using the Canva Application and to find out students' KKM achievement using the Akidah Akhlak LKPD Using the Canva Application in class VII at MTs. Darul A'mal Metro City. This study uses Research and Development (RnD) in the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques in this study used questionnaires, interviews, and documentation. Based on the data analysis, the researcher got the final results from the validation of media experts, with an average of 87% in the very feasible category, and material experts, with an average of 86% in the very feasible category. The overall results show that the Akidah Akhlak LKPD product using the Canva application is very suitable for use in the Akidah Akhlak material learning process. The study results show that LKPD Akidah Akhlak using the Canva application can improve learning abilities, as shown by the increased interest in reading and KKM students.